Environmental Health Risk Assessment of NO2 Ambient Level and Toll Collectors Officer‘S Health Complaints - Febri Ayu Wulaningtyas (Universitas Airlangga, 2018)
Nowadays NO2 ambient level has been increasing in year to year. Pollutant level which has over level from the threshold limit will give some of bad effects to environment and human health. The aim of this study was to measure the environmental health risk assessment of NO2 ambient level and toll collectors officer ‘s health complaints at Toll gate of Dupak 1, Surabaya. This was descriptive study with cross sectional design. Interview was done to 17 respondents who met the conclusion criteria to know respondent's health complaints. Independent variables were NO2 level, sex, age, weight, length of work in a day and work period. Where as dependent variabel was toll collectors officer's of Toll gate of Dupak 1 Surabaya health complaints, such as: headache, eyes irritation, red eyes, hard to breath and cough. Result shown that respondent with 62 weight average were not safe work in Toll gate of Dupak 1 if the air velocity was 0.83 m3/ hour, in 8 hour/day, average of time in 350 days/year for next 30 years if NO2 level had maximal concentration 0.1183 ppm (RQ > 1). The majority of health complaints were cough 82.3%, red eyes 70.5%, eyes irritation 64.7%, headache 53%, and hard to breath 47%. However risk quotient of NO2 exposure was not safe for respondent with pollutants level appropriate to the measurement result and should have preventive action like as consume vitamin C and E and use N95 and regulations for using masker and not smoking while work have to applied strictly.